In vitro development of B lymphocytes from long-term cultured precursor cells. - Denis, K A (1986)
An in vitro system for the study of B-lymphocyte differentiation from precursor elements has been established. Two separate sets of culture conditions are utilized to control B-lymphocyte precursor growth versus differentiation. The first, modeled after the bone marrow culture system of Dexter and colleagues [Dexter, T. M. & Testa, N. G. (1976) in Methods in Cell Biology, ed. Prescott, D. M. (Academic, New York), Vol. 14, pp. 387-395], allows precursor replication whereas the second set of culture conditions is permissive for differentiation to more mature members of the B-lymphocyte lineage. The shift from one set of conditions to the other allows us to follow the kinetics of this differentiation from precursor cells to pre-B and B lymphocytes over a 5-week period. The resulting population of B-lineage cells synthesizes heterogeneous immunoglobulin molecules as analyzed by two-dimensional gel electrophoresis and has a heterogeneous array of immunoglobulin gene rearrangements, suggesting an origin from very early uncommitted precursors. This in vitro system will allow the study of genes that regulate B-lymphocyte differentiation and will aid in the isolation of the cellular intermediates in the B-cell developmental pathway.